An in vitro model to study suction events by a ventricular assist device: validation with clinical data - Rocchi, Maria; Gross, Christoph; Moscato, Francesco; Schlöglhofer, Thomas; Meyns, Bart; Fresiello, Libera (Frontiers in Physiology, 2023)
Ventricular assist devices (LVADs) are a valuable therapy for end-stage heart failure patients.However, some adverse events still persist, such as suction that can trigger thrombus formation and cardiac rhythm disorders. The aim of this study is to validate a suction module (SM) as a test bench for LVAD suction detection and speed control algorithms. The SM consists of a latex tube, mimicking the ventricular apex, connected to a LVAD. The SM was implemented into a hybrid in vitro-in silico cardiovascular simulator. Suction was induced simulating hypovolemia in a profile of a dilated cardiomyopathy and of a restrictive cardiomyopathy for pump speeds ranging between 2500 and 3200 rpm. Clinical data collected in 38 LVAD patients were used for the validation. Clinical and simulated LVAD flow waveforms were visually compared. For a more quantitative validation, a binary classifier was used to classify simulated suction and